A Performant Dry Reforming Catalytic System Elaborated from the Reductive Decomposition of BaNi2V2O8. Issue 18 (7th November 2016) - Guerrero‐Caballero, Jesus; Löfberg, Axel; Mentré, Olivier; Kane, Tanushree; Pussacq, Tanguy; Roussel, Pascal; Huvé, Marielle; Trentesaux, Martine; Gardoll, Olivier; Kabbour, Houria
Abstract: The reductive decomposition of BaNi2 V2 O8 leads to a Ni‐supported catalyst composed by an intimate blend of Ba3 (VO4 )2 /Ni/BaV10 O15 . High activity for the Dry Reforming of Methane (DRM) is attained with 85 % conversion for CH4 and CO2, as well as a very good stability in time and a high selectivity with H2 /CO=0.9 and negligible carbon deposition. A rich redox and optimal oxide‐metal interactions provide a unique and promising catalytic system. Abstract : The reductive decomposition of BaNi2 V2 O8 leads to the Ni‐supported catalyst composed by the intimate blend Ba3 (VO4 )2 /Ni/BaV10 O15 . High activity for the Dry Reforming of Methane (DRM) is attained with 85 % conversion for CH4 and CO2 . This catalytic system exhibit a very good stability in time and a high selectivity.